The Effect of Boiling on Nitrite Content in Green Mustard (Brassica rapa var. parachinensis) with Soil And Hydroponic Growing Media - 'Aisy, ‘Afif ‘Aziizah Rihhadatul; Aina, Ganea Qorry; Farpina, Eka (Indonesian Journal of Food Technology, 2025)
Background: Nitrite is a compound that has the potential to pose health risks if consumed in excessive amounts, including through the formation of carcinogenic nitrosamine compounds and disruption of oxygen transport due to methemoglobin formation. The nitrite content in green vegetables is influenced by various factors, including the cultivation system and processing processes before consumption, one of which is boiling. Purpose:This study aims to determine the effect of soil and hydroponic growing media on the nitrite levels of green mustard (Brassica rapa var. parachinensis) after boiling. Method: This study used an experimental design with green mustard samples cultivated in soil and hydroponic media. The samples were boiled for 3 minutes, then the nitrite levels were analyzed using the Griess method with a UV–Vis spectrophotometer according to SNI 06-6989.9-2004. Data analysis was carried out using normality tests, homogeneity tests, and independent t-tests. Result: The results showed that the initial nitrite levels of hydroponic green mustard were higher than those of green mustard from soil media. After boiling, the nitrite content in the soil-grown mustard greens was 20.61 mg/kg with a reduction percentage of 88.91%, while in the hydroponic mustard greens it was 71.05 mg/kg with a reduction percentage of 70.71%. The results of statistical tests showed a significant difference (p < 0.05) between the two growing media. This study concluded that the type of growing media significantly affected the nitrite content of the mustard greens after boiling, where the soil media produced lower nitrite levels compared to the hydroponic media.